Network disruption detected in KH (Cambodia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Cambodia. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: KH-2026-0002. Severity: critical. Confidence: 70%